Right atrial function by speckle tracking echocardiography in atrial septal defect: Prediction of atrial fibrillation. Issue 10 (16th October 2018) - Vitarelli, Antonio; Mangieri, Enrico; Gaudio, Carlo; Tanzilli, Gaetano; Miraldi, Fabio; Capotosto, Lidia
Abstract : Background: Most antiarrhythmic interventional therapies for atrial fibrillation (AF) have been provided with special focus on the treatment of left‐sided valvular disease and enlarged left atrium but few studies have assessed AF associated with congenital heart disease and dilated right atrium. Hypothesis: We hypothesized that right atrial (RA) function assessed by two‐dimensional (2DSTE) and three‐dimensional (3DSTE) speckle‐tracking echocardiography in patients with atrial septal defect (ASD) before and after percutaneous trancatheter closure could predict paroxysmal atrial fibrillation (PAF) development. Methods: Seventy‐three patients with hemodynamically significant secundum ASD were prospectively studied and followed up for 6 months after occluder insertion and compared with a normal age‐matched group ( n  = 73). A subgroup of 17 patients who developed PAF after device implantation was also studied. RA peak global longitudinal strain (PS) was determined using 2DSTE. Standard deviations (SDs) of times to peak strain (TPS) were calculated as indices of dyssynchrony. RA volumes, emptying fraction (EF), and expansion index (EI) were determined using 3DSTE. Results: RA‐PS, EF, and EI (pre‐closure values) were reduced in patients with atrial devices compared with controls, and further reductions were observed in patients with PAF. Pre‐closure 3D‐RA‐EI ( P  = 0.009) and RA‐TPS ( P  = 0.023) were independent predictors of PAF by multivariate analysis after adjustment for age and left atrial dysfunction. The areas under the ROC‐curve (AUC) for 3D‐RA‐EI, RA‐PS, RA‐TPS (pre‐closure values) showed high discriminative values(from 0.76 to 0.85) in predicting PAF. By combining 3D‐RA‐EI and RA‐TPS, the AUC increased to 0.90. Conclusions: Two‐dimensional and three‐dimensional speckle tracking echocardiography was clinically helpful in ASD patients in revealing right atrial dilatation and dysfunction pre‐existent to device closure and associated with PAF development. RA parameters had a higher association with PAF compared to both the size of the implanted device and left atrial indices.